Fecal-Oral Transmission of COVID-19 in India - Goff, Allyson; Ahmad, Akram; Patel, Isha (Journal of Pharmacy Practice and Community Medicine)
Although the spread of COVID-19 through droplets, surface contact and aerosolized transmission has been well-publicized, the fecal-oral route is yet another identified method of transmission. According to a meta-analysis by the New England Journal of Medicine, it was found that fecal viral shedding continues throughout the disease, even after nasopharyngeal tests appear negative. Moreover, gastrointestinal symptoms seem to be common for COVID-19 patients, with a prevalence of approximately 18%.[1,2] It was also found that patients with digestive symptoms experience significantly longer hospital stays.[3] As India’s number of COVID-19 cases continues to increase, concerns about fecal-oral transmission are being raised in a country that has the highest open defecation rates in the world, where approximately 620 million people defecate in the open. It is a problem that comes with severe public health consequences, including diarrhea, high child mortality, spread of diseases, malnutrition and stunting of growth.[4] Public health officials should be concerned about how this will affect India’s transmission of COVID-19.